The Role of Local Government in the Development of Urban Tourism in Bali from the Perspective of New Public Service and Public Service - Anak Agung Istri Anom Sri Widya Shanti; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The development of urban tourism in Bali represents a dynamic process of urban development that requires an active role of local governments in policy formulation and public service delivery. This study aims to analyze the role of local government in the development of urban tourism in Bali from the perspective of New Public Service and public service theory. A qualitative approach with a case study design was employed, focusing on Denpasar City. Data were collected through in-depth interviews, field observations, and document analysis of tourism-related policies and regulations. The data were analyzed thematically by linking empirical findings to the core principles of New Public Service, including public interest orientation, citizen participation, collaboration, and accountability. The findings indicate that local government has played a strategic role in planning and providing supporting facilities for urban tourism; however, the implementation of public services still faces challenges related to institutional capacity, fragmented authority, and limited public participation in decision-making processes. The study concludes that strengthening the New Public Service paradigm is essential to improve the quality of public services and to promote sustainable, inclusive, and equitable urban tourism development in Bali. Keywords: Bali, Local Government, New Public Service, Public Services, Urban Tourism